A Study on Women’s Perception of Glass Ceiling in the Private Organizations, Pokhara - Rana, Barsha (Journal of Nepalese Business Studies, 2008)
The study is intended to explore women’s perception of glass ceiling in the private organizations of Pokhara. Hundred women with different age groups working in different private organizations of Pokhara were taken as the sample. Their perception on the disparate treatment of women in organizations, behavior of their male colleagues towards them, the role of their family members in their professional growth, perception of role conflict and their aspiration towards their career advancements were asked and have been analyzed to find out if women perceive the existence of glass ceiling. In this regard, viewpoints of their male counterparts have also been taken into consideration. The Journal of Nepalese Business Studies Vol. IV, No. 1(2007) pp. 83-87